How to Measure and Identify the Ultimate Improvement Required for Customer Satisfaction - Sihombing, Haeryip; M.Y., Yuhazri; S.H., Yahaya (Global Engineers and Technologists Review, 2012)
In current hypercompetitive markets, customer satisfaction is one of major requirements that enable the company to generate some benefits to their business. This is also including the relationship with the customers as a good foundation for the creation of loyalty and repeat purchase of customers. However, the customer requirements are much more technically complex than in consumer market, especially in service sector. On the other hand, the analysis of importance and performance assumed on Kano method to measure customer satisfaction also lead to misleading the implications of customer satisfaction since some scholars use this technique into symmetric and linear relationships between attribute level performances. In this study, we poposes the approach on how to find the priority improvement or the most significant element required for improvement based on Kano method as a measurement basis ; using Kano manipulating graph, ranking level, and then a simplification approach toward the graphs to enable the priorities / significant element required for improvement determined and justified. To justify the approach proposed, some trials carried out in service companies as the case of study.